The Influence Of The Challenges Of Applying Artificial Intelligence On Students Business Creativity In The Entrepreneurship Study Program - Mochamad Farhan; Muhammad Ahmi Husein (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examines the influence of Artificial Intelligence (AI) usage challenges namely elaboration fluency, effectiveness, and ethical concerns on students’ creativity exploration in entrepreneurship education. A quantitative approach with a cross-sectional design was employed through a survey of 344 students from the Entrepreneurship Study Program at Universitas Pembangunan Nasional “Veteran” Jawa Timur. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to simultaneously assess the relationships among constructs. The findings reveal that ethical challenges of AI have a positive and significant effect on students’ creativity exploration, while effectiveness and elaboration fluency challenges do not show significant effects. These results indicate that ethical dimensions play a more prominent role than technical aspects in shaping technology-based creative exploration processes. Theoretically, this study extends the understanding of human–AI interaction in the context of creativity and knowledge-driven innovation. Practically, the findings provide insights for educational institutions to integrate AI ethics literacy into entrepreneurship education in order to support responsible and sustainable creativity exploration. This study contributes empirically by highlighting the multidimensional role of AI challenges in shaping students’ creativity and innovation processes.